The involvement of male opposition parliamentarians in the 13th parliament, 2013-18 - Amirul Azam Asri,; Rosyidah Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Gender is defined as personality, behavior, value, power, influence, and the role played by the two genders known as men and women. However, the problem of gender inequality often occurs in any country and occurs in various sectors such as society, economy, education, medicine, and politics. Many previous scholars made studies on women’s involvement in the political arena, but a lack of previous researchers focused on men’s involvement in the political arena. This is because in many countries the involvement of males in politics is quite high compared to women. While in Malaysia too, there is a huge gap between the involvement of men and women in the political landscape. Therefore, this article will focus on the involvement of male opposition parliamentarians in the 13th Parliament starting from 2013 until 2018. The objective of this study is to identify the issues debated by the male opposition in the 13th Parliament. The second objective is to study the behavior of the opposition in the 13th parliament and the third objective is to identify the involvement of the male opposition in the 13th parliament. This study uses a qualitative approach by using document analysis as the main method obtained from the parliamentary Hansard. According to the empirical result, there is a connection between the number of parliamentary seats and Pakatan Harapan (PH)’s victory in the previous general election (GE). The opposition acted actively in playing their role as a legislative, and representative. Interestingly this study will provide additional interest and information to several parties. Among them are the community, politicians as well as researchers. This study will give exposure to the community of the opposition parties, especially in Malaysia. Through this study, is expected that the researcher will be able to provide knowledge and information related to the opposition, especially male opposition.